Inflammatory Phenotypes of Cough Variant Asthma as Response Predictors to Anti-Asthmatic Therapy - Rybka-Fraczek A; Dabrowska M; Grabczak EM; Bialek-Gosk K; Klimowicz K; Truba O; Nejman-Gryz P; Paplinska-Goryca M; Krenke R (Dove Medical Press, 2022)
Aleksandra Rybka-Fraczek, Marta Dabrowska, Elzbieta M Grabczak, Katarzyna Bialek-Gosk, Karolina Klimowicz, Olga Truba, Patrycja Nejman-Gryz, Magdalena Paplinska-Goryca, Rafal Krenke Department of Internal Medicine, Pulmonary Diseases and Allergy, Medical University of Warsaw, Warsaw, PolandCorrespondence: Marta Dabrowska, Tel +48 22 599 2599, Fax +48 22 599 1069, Email mdabrowska@mp.plBackground: Eosinophilic inflammatory phenotype was thought to be the most common phenotype of cough variant asthma (CVA), nevertheless other phenotypes were also reported.Purpose: The study aimed to analyze the inflammatory phenotypes of CVA in relation to treatment response to the stepwise anti-asthmatic treatment.Patients and Methods: The study included 45 patients with chronic cough (CC) and suspicion of CVA (normal chest X-ray, presence of bronchial hyperresponsiveness and no history of wheezing or dyspnea) in whom induced sputum was successfully collected. Based on the cellular composition of the sputum, patients were divided into major inflammatory phenotypes: eosinophilic, neutrophilic, paucigranulocytic or mixed granulocytic. A stepwise treatment, including inhaled corticosteroids with long-acting β2-agonist, montelukast and short-term therapy with prednisone was initiated. Good treatment response was defined as the reduction in cough severity at least 20 mm from the baseline in visual analogue scale and improvement in cough-related quality of life assessed by the Leicester cough questionnaire at least 1.3 points after any of three steps.Results: Finally, 40/45 (88.9%) patients improved after therapy. Eosinophilic asthma was found in 13/40 (32.5%) patients, neutrophilic in 6/40 (15.0%) and paucigranulocytic pattern in 21/40 (52.5%) patients. No one demonstrated a mixed granulocytic phenotype. The response to the treatment was similar in all groups. However, the reduction in cough severity was inversely related to the percentage of sputum neutrophils (r = − 0.44, P = 0.003). We showed that the percentage of neutrophils in sputum > 46% may be considered as a predictor of poor response to anti-asthmatic therapy.Conclusion: The diversity of inflammatory phenotypes with paucigranulocytic preponderance was found in subjects with CVA. The response to anti-asthmatic treatment in patients with CVA was not related to the inflammatory phenotype. High neutrophil count in sputum may predict poor response to anti-asthmatic therapy in patients with CC and bronchial hyperresponsiveness.Keywords: bronchial hyperresponsiveness, chronic cough, cough variant asthma, paucigranulocytic, neutrophils, sputum induction